Tumor-Derived Microvesicles Enhance Cross-Processing Ability of Clinical Grade Dendritic Cells - Dionisi, Marco; De Archangelis, Claudia; Battisti, Federico; Rahimi Koshkaki, Hassan; Belleudi, Francesca; Zizzari, Ilaria Grazia; Ruscito, Ilary; Albano, Christian; Di Filippo, Alessandra; Torrisi, Maria Rosaria; Benedetti Panici, Pierluigi; Napoletano, Chiara; et al. (Frontiers in Immunology, 2018)
Tumor cells release extracellular microvesicles (MVs) in the microenvironment to deliver biological signals to neighbouring cells as well as to cells in distant tissues. Tumor-derived MVs appear to play contradictory role promoting both immunosuppression and tumor growth and both evoking tumor specific immune response. Recent evidences indicate that tumor-derived MVs can positively impact Dendritic Cells (DCs) immunogenicity by reprogramming DC antigen processing machinery and intracellular signaling pathways, thus promoting anti-tumor response. DCs are considered pivot cells of the immune system due to their exclusive ability to coordinate the innate and acquired immune responses, cross-present exogenous antigens and prime naïve T cells. DCs are required for the induction and maintenance of long-lasting anti-tumor immunity and their exploitation has been extensively investigated for the design of anti-tumor vaccines. However, the clinical grade culture conditions that are required to generate DCs for therapeutic use can strongly affect their functions. Here, we investigated the immunomodulatory impact of MVs carrying the MUC1 tumor glycoantigen (MVsMUC1) as immunogen formulation on clinical grade DCs grown in X-VIVO 15 (X-DCs). Results indicated that X-DCs displayed reduced performance of the antigen processing machinery in term of diminished phagocytosis and acidification of the phagosomal compartment suggesting an altered immunogenicity of clinical grade DCs. Pulsing DCs with MVsMUC1 restored phagosomal alkalinization, triggering ROS increase. This was not observed when a soluble MUC1 protein was employed (rMUC1). Concurrently, MVsMUC1 internalization by X-DCs allowed MUC1 cross-processing. Most importantly, MVsMUC1 pulsed DCs activated IFNγ response mediated by MUC1 specific CD8+ T cells. These results strongly support the employment of tumor-derived MVs as immunogen platforms for the implementation of DC-based vaccines.